Technology and Globalisation Networks of Experts in World History (Palgrave Studies in Economic History,, 2018)
This book examines the role of experts and expertise in the dynamics of globalisation since the mid-nineteenth century. It shows how engineers, scientists and other experts have acted as globalising agents, providing many of the materials and institutional means for world economic and technical integration. Focusing on the study of international connections, Technology and Globalisation illustrates how expert practices have shaped the political economies of interacting countries, entire regions and the world economy. This title brings together a range of approaches and topics across different regions, transcending nationally-bounded historical narratives. Each chapter deals with a particular topic that places expert networks at the centre of the history of globalisation. The contributors concentrate on central themes including intellectual property rights, technology transfer, tropical science, energy production, large technological projects, technical standards and colonial infrastructures. Many also consider methodological, theoretical and conceptual issues. David Pretel is Research Fellow at the Centre for Historical Studies, Colmex, The College of Mexico, Mexico. He specialises in the global history of technology, international economic history and the intellectual history of capitalism, with an ever-increasing interest in Latin American history. Lino Camprubí is Research Fellow at the Center for the History of Science, UAB Barcelona, Spain. He has been a research scholar at the Max Planck Institute for the History of Science, Germany, and a visiting lecturer at University of Chicago, USA. .